2004
DOI: 10.1111/j.1467-7652.2004.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of tailor‐made fructans in sugar beet by expression of onion fructosyltransferase genes

Abstract: SummaryThe consumption of fructans as a low caloric food ingredient or dietary fibre is rapidly increasing due to health benefits. Presently, the most important fructan source is chicory, but these fructans have a simple linear structure and are prone to degradation. Additional sources of high-quality tailor-made fructans would provide novel opportunities for their use as food ingredients. Sugar beet is a highly productive crop that does not normally synthesize fructans. We have introduced specific onion fruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 24 publications
3
22
0
1
Order By: Relevance
“…In sugar beet, introduction of an enzyme of fructan synthesis from onion resulted in substantial conversion of the sucrose content of the storage root to fructans of low molecular mass (Weyens et al, 2004). However, this apparently did not result in greater import of sucrose into the roots: total carbohydrate content was not affected.…”
Section: Increasing Sucrose Contentmentioning
confidence: 99%
“…In sugar beet, introduction of an enzyme of fructan synthesis from onion resulted in substantial conversion of the sucrose content of the storage root to fructans of low molecular mass (Weyens et al, 2004). However, this apparently did not result in greater import of sucrose into the roots: total carbohydrate content was not affected.…”
Section: Increasing Sucrose Contentmentioning
confidence: 99%
“…This makes the Mll promoter a very good candidate for biotechnological applications. For example, a higher tissue specific activity of introduced fructosyltransferases may be achieved in roots to convert sucrose to low molecular fructans (Weyens et al 2004) The promoter reporter gene fusions transformed into tobacco also show a specific expression profile. The expression of the Mll and Tlp promoters in root and hypocotyl support the conclusion that storage root expressed genes require regulatory elements for these tissues because the beet root comprises hypocotyl and primary root tissue (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the introduced Helianthus tuberosus 1-sucrose:sucrose fructosyl transferase converted almost all sucrose in the storage root of sugar beet to low molecular fructans (Sevenier et al 1998). A different approach achieved the conversion of sucrose to onion-type fructans by introducing onion fructosyltransferases under the control of the Arabidopsis ubiquitin 3 promoter into transgenic sugar beets (Weyens et al 2004). Fructosyltransferase activity was detected in leaf and root tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been reported that expression of plant fructosyltransferase transgenes in variety of transgenic plants induces the synthesis of fructans and fructooligosaccharides or increases their contents (Hellwege et al 1997;Hisano et al 2004;Jenkins et al 2002;Kawakami et al 2008;Ritsema and Smeekens, 2003;Sévenier et al 1998;Stoop et al 2007;Weyens et al 2004). Successful accumulation of bacterial fructan (levan; β-2,6-linked fructan) has been also achieved by the introduction of bacterial levan sucrase into transgenic plants (reviewed by Cairns 2003).…”
Section: High Performance Liquid Chromatography (Hplc) Analysesmentioning
confidence: 99%